Improved adhesion and interface ohmic contact on n-type 4H-SiC substrate by using Ni/Ti/Ni - 韩林超 申华军 刘可安 王弋宇 汤益丹 白云 许恒宇 吴煜东 刘新宇 (Journal of semiconductors, 2014)
The Ni/Ti/Ni multilayer ohmic contact properties on a 4H-SiC substrate and improved adhesion with the Ti/Au overlayer have been investigated. The best specific contact resistivity of 3.16 × 10^-5 Ω.cm^2 was obtained at 1050 ℃. Compared with Ni/SiC ohmic contact, the adhesion between Ni/Ti/Ni/SiC and the Ti/Au overlayer was greatly improved and the physical mechanism under this behavior was analyzed by using Raman spectroscopy and X-ray energy dispersive spectroscopy （EDS） measurement. It is shown that a Ti-carbide and Ni-silicide compound exist at the surface and there is no graphitic carbon at the surface of the Ni/Ti/Ni structure by Raman spectroscopy, while a large amount of graphitic carbon appears at the surface of the Ni/SiC structure, which results in its bad adhesion. Moreover, the interface of the Ni/Ti/Ni/SiC is improved compared to the interface of Ni/SiC.